Lactate Ringer’s Versus Normal Saline in the Management of Acute Pancreatitis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Guzmán-Calderón, Edson (2022)
Background: Fluid therapy plays a critical role in the management of acute pancreatitis. Normal saline (NS) is commonly used in these patients. However, Lactate Ringer’s (LR) has also been shown to be useful for this condition. Aim: To assess the effect of LR compared to NS in patients with acute pancreatitis. Methods: We searched in three electronic databases from inception to December 2020 for randomized controlled trials (RCTs). Outcomes were mortality, intensive care unit (ICU) admission, hospital stay, and Systemic Inflammatory Response Syndrome (SIRS) at 24, 48, and 72 h. The risk of bias was assessed using the Risk of Bias 2.0 tool. All meta-analyses were performed using a random-effects model. Results: Four RCTs comprising 248 patients were included. The mean age ranged from 42.3 to 63.8 years and 49% of patients were men. Patients treated with LR had similar risk of mortality (risk ratio [RR], 0.53; 95% confidence interval [CI], 0.09–3.00) and SIRS at 24 h (RR, 0.69; 95% CI, 0.32–1.51), 48 h (RR, 0.80; 95% CI, 0.46–1.41), and 72 h (RR, 0.68; 95% CI, 0.37–1.25) compared to NS. LR had significantly lower hospital stay (mean difference, − 1.10; 95% CI, − 1.92 to − 0.28) and lower risk of ICU admission (RR, 0.42; 95% CI, 0.20–0.89) compared to NS. The risk of bias was low in nearly all RCTs. Conclusion: No differences were found in the mortality and SIRS at 24, 48, and 72 h in patients treated with LR and NS. In contrast, patients who received LR had a lower risk of ICU admission and lower hospital stay than NS.